2016
DOI: 10.1002/nme.5272
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid meshing using constrained Delaunay triangulation for viscous flow simulations

Abstract: SUMMARYIn this paper, we present a generalized prismatic hybrid meshing method for viscous flow simulations. One major difficulty in implementing a robust prismatic hybrid meshing tool is to handle boundary layer mesh collisions, and normally an extra data structure (e.g. quadtree in two-dimensional and octree in threedimensional) is required. The proposed method overcomes this difficulty via an heuristic approach, and it only relies on constrained delaunay triangulation/tetrahedralization (CDT). No extra data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Presently, the most prevailing approaches for computing marching directions are those based on the analysis of the manifold of a point [16][17][18][19][20][21]. The manifold of a point here refers to the set of front faces adjacent to the point, and these front faces are thus named manifold faces of that point.…”
Section: On Computation Of Marching Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Presently, the most prevailing approaches for computing marching directions are those based on the analysis of the manifold of a point [16][17][18][19][20][21]. The manifold of a point here refers to the set of front faces adjacent to the point, and these front faces are thus named manifold faces of that point.…”
Section: On Computation Of Marching Directionsmentioning
confidence: 99%
“…The solution of that problem could result in the 'best' marching direction at a point by providing an optimal angle property for the next layer of elements that meet at that direction. Nevertheless, it was reported that if the marching direction at each point of a front face was computed in a locally optimal fashion [20,21], it still might not be optimal for the prism carried by the face. Therefore, some kind of global smoothing must be performed after the initial computation of the marching directions.…”
Section: On Computation Of Marching Directionsmentioning
confidence: 99%
See 3 more Smart Citations